Comparison of Prenatal and Neonatal Outcomes of Selective Fetal Growth Restriction in Monochorionic Twin Pregnancies with or Without Twin-to-Twin Transfusion Syndrome After Radiofrequency Ablation - Fatemeh Rahimi-Sharbaf; Mahboobeh Shirazi; Fatemeh Golshahi; Zohreh Salari; Mansoureh Haghiri; Marjan Ghaemi; Hanieh Feizmahdavi (Iranian Journal of Medical Sciences, 2022)
Background: This study aimed to investigate and compare the prenatal and neonatal outcomes of monochorionic twin pregnancies complicated with fetal growth restriction (sFGR) with or without twin-to-twin transfusion syndrome (TTTS) after cord occlusion by radiofrequency ablation (RFA).Methods: This prospective cross-sectional study was conducted in women with monochorionic twin pregnancies of 16 to 26 weeks of gestational age (GA) in an academic hospital from 2016 to 2020. Demographic and obstetrical characteristics such as cervical length, GA of RFA and delivery, amnioreduction, cesarean section (C/S) rate, and maximum vertical pocket as well as prenatal, neonatal, and maternal outcomes were evaluated and compared between groups using Statistical Package for the Social Sciences (SPSS). Mann-Whitney U test or independent t test was used for quantitative data and Chi square test was applied for comparing qualitative variables. The significance level of tests was 0.05.Results: Totally 213 (106 sFGR and 107 TTTS+sFGR) cases were enrolled. The mean of maternal age (P=0.787), body mass index (P=0.932), gestational age at RFA (P=0.265), as well as gestational age of delivery (P=0.482), and C/S rate (P=0.124) were not significant between the two groups, but a significant difference (P<0.001) in cervical length was observed between the two groups. No significant differences were found in newborn and fetal outcomes such as fetal demise (P=0.827), PPROM (P=0.233), abortion (P=0.088), and admission to intensive care unit (P=0.822) between the groups.Conclusion: Although worse fetal and neonatal outcomes were expected in the TTTS+sFGR group after RFA, no significant difference was observed between groups.